أمكانية تعزيز أبعاد تطوير المنتج من خلال مكونات نظام المعلومات التسويقية : دراسة استطلاعية لاراء المدراء في الشركة الوطنية لصناعة الاثاثا المنزلي في الموصل - د. أكرم احمد الطويل; غانم محمود احمد الكيكي (PROSPECTIVE RESEARCHES, 2023)
The study strives for determining the role of marketing information system that plays it on sustaining a dimensions of product development in the national company of housing furniture manufacturing, where the marketing information system are considered one of the important systems in the company and by it the company can be successful to develop its product, and achieve its goals with the efficiency and effectiveness. Because of the Limits of the studies which deal with relationship and effect between these variables and especially in the Iraqi environment, the two researchers sought for including their present study these dimensions with their variables within total framework as an attempt for studying the relationship and impact between them: Generally, the study tries to answer the following inquiries: 1- Is there a clear imagination for the managers in the national company of housing furniture manufacturing about the concept and Components of marketing information system in addition, the concept and dimensions of product development? 2- What is the nature of the relationship and effect between the Components the Marketing Information System and Dimensions of Product Development for company under study? The study has reached to a set of conclusions, and the most important ones are: - There is a significant relationship between the Components the Marketing Information System and Dimensions of Product Development. - There is a significant effect for Components the Marketing Information System in the Dimensions of Product Development. Depending on the conclusions, which the study achieved, a set of harmonized suggestions with these conclusions have been presented.